Animal models for schizophrenia - Pletnikov, Mikhail (Henry Stewart Talks, 2013)
Animal models for schizophrenia, Animal models of psychiatric disorders, Non-genetic animals models, genetic animal models, DISC1 anima models, Weaknesses of the current animal models for schizophrenia, Future directions in developing animal models for schziophrenia